Resistance formation to nitro drugs in Giardia lamblia: No common markers identified by comparative proteomics. (April 2019) - Müller, Joachim; Braga, Sophie; Heller, Manfred; Müller, Norbert
Abstract: In order to elucidate the question whether resistance to nitro drugs in G. lamblia is due to common resistance markers, trophozoites of three resistant G. lamblia strains, namely C4, 1062ID10, and 713M3 were grown in the presence of the two nitro drugs metronidazole and nitazoxanide and compared to their corresponding wild-types WBC6, 106, and 713 by mass spectometry shotgun analysis of their proteomes. Depending on the strain and the nitro drug, more than 200 to 500 differentially expressed proteins were identified, but there were no common patterns across strains and drugs. All resistant strains underwent antigenic variation with distinct surface antigens like variant surface proteins or cysteine rich proteins depending on strain and nitro compound. A closer look on enzymes involved in nitroreduction and detoxification of nitro radicals, NO or O2 suggested the existence of distinct strategies for each drug and each strain. Therefore, we conclude that resistance to nitro drugs in G. lamblia is not correlated with a specific pattern of differentially expressed proteins and therefore seems not to be the result of a directed process. Graphical abstract: Image 1 Highlights: Is resistance to nitro drugs in G. lamblia due to common resistance markers? Three resistant strains were grown in the presence of two nitro drugs separately and compared to wild-types by MS shotgun analysis. More than 200 to 500 differentially expressed proteins identified depending on strain and drug. No common patterns across strains and drugs. Strain specific antigenic variation and strategies linked to nitro reduction.